A Rare Case of Type 1 Neurofibromatosis-Associated Unilateral Gigantomastia: A Case Report and Literature Review. (17th November 2020) - Phan, Kim; Vignarajah, Muralie; Huq, Nasimul
Neurofibromatosis type 1 (NF1) is an autosomal dominant disorder characterized by the formation of benign nerve sheath tumours known as neurofibromas. A 28-year-old female presented with a large neurofibroma extending from the elbow of the right arm into the axilla and across the right breast. A mastectomy was performed to excise 4 kg of tissue with an immediate flap reconstruction. Post-operatively, the patient's hemoglobin levels dropped significantly due to excessive blood loss, but the patient was discharged by post-operative day 5 with no additional complications. This study raises awareness for NF1, describes possible complications that may arise following excision of highly vascularized neurofibromas, and outlines possible techniques for breast reconstruction.